1885-86 Wash. Terr. Laws 81-82 - (:unkn) unknown (My University, 1886)
Prohibited the concealed carry of any revolver, pistol, or other firearms, or any knife, dirk, dagger, sling shot, metal knuckles, any instrument by the use of which injury could be inflicted upon the person or property of another. Violators guilty of a misdemeanor, fined by not less than twenty but no more than one hundred dollars, or imprisonment not more than thirty days, or both fine and imprisonment.
Keywords: CARRY - CONCEALED